Increasing the Principal’s Leadership in Student Achievement in the Science Learning at Sebatik Vocational School - Mariani, Isma; Suyud (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to identify and analyze efforts to improve the principal’s leadership in student achievement in science learning at Sebatik Vocational School using a qualitative approach. The problem of limited laboratory facilities and science equipment is the main focus in this research. The data analysis method is based on qualitative data analysis techniques developed by Miles and Huberman. There were 4 respondents in this study, namely, school principals, teachers and students. Data collection techniques through interviews, observation and documentation. The results of this research found that efforts to improve school principal leadership include advocacy for budget allocations, initiatives to expand access to teaching materials, and close communication between stakeholders. The hope is to improve responsive and inclusive leadership strategies in the quality of science learning at Sebatik Vocational School and improve student achievement in science subjects.